Resisted jumps in complex training its effects on countermovement jump performance - Papa, Emmanuel Liberato V.; Pagaduan, Jeffrey C. (2014)
The purpose of this study was to identify the effect of a heavy-load lower body exercise paired with assisted countermovement jumps in complex training (CT). Seven female national dragonboat athletes (age: 27.4 ± 3.26 yrs; height: 163.6 ± 6.42 cm; weight: 64.3 ± 3.74; body fat %: 26.3 ± 3.52; 5 RM = 44.8 ± 1.11 kg) volunteered to participate in the study. They performed two counterbalanced randomized crossover sessions that consisted a heavy load dumbbell goblet squat (DGS) paired with resisted countermovement jumps (CT-R) and DGS paired with body weight countermovement jumps (CT-BW). Experimental sessions were separated by 7 days. Pre, post-1 (-4 min), post-2 (-8 min) hands-on-waist countermovement jump (CMJ) were utilized for analyses. Two-way repeated measures ANOVA revealed a non-significant interaction between intervention and time at F(2, 12) =0.642, p-0.543, partial eta squared = 0.097. In conclusion, CT-R posted no significant difference in hands-on-waist CMJ with CT-BW across time measurements in the study.
Keywords: Exercise tests; Muscle strength -- Testing; Women athletes -- Ability testing